PENGARUH E-COMMERCE SHOPEE SEBAGAI MEDIA BELANJA FASHION ONLINE - Olivia Nathania Sekar Putri; Dian Sudiantini, Alfonsa Susanti Ina, Azka Ribka Davianti, Febby Liu (CV. Adiba Aisha Amira, 2024)
This research aims to analyze the influence of the Shopee e-commerce platform as a medium for online fashion shopping. In the ever-growing digital era, Shopee has become one of the largest e-commerce platforms in Indonesia, providing various fashion products that can be easily accessed by consumers. This research uses a quantitative method by distributing questionnaires to a number of respondents who actively shop for fashion through Shopee. The research results show that the factors of ease of access, product variety and promotional features oflered by Shopee significantly influence consumer decisions when shopping for fashion online. Apart from that, customer satisfaction with Shopee services also plays an important role in increasing consumer loyalty. This research is expected to provide insight for online fashion industry players in developing eflective marketing strategies and improving consumer shopping experiences on e-commerce platforms.